(untitled) - Kador, John (Hoboken, NJ., 2002)
This book tells the exciting story of how Charles Schwab revolutionized the financial services industry and shook up Wall Street forever. It is also an essential read for any aspiring entrepreneur
Keywords: Charles Schwab corporation,Stockbrokers,Tập đoàn Charles Schwab,Môi giới chứng khoán; History,History,Lịch sử; New York (State),New York (Hoa Kỳ)